2021
DOI: 10.1007/s11069-021-04879-3
|View full text |Cite
|
Sign up to set email alerts
|

Marine storms in coastal tourist areas of the Canary Islands

Abstract: The small island areas oriented to coastal tourism are highly vulnerable to marine storms, given the fluctuation of this economic sector and the increase in its exposure due to the increasing anthropogenic presence on the coastline. In this context, the storms between 1958 and 2017 are studied here in the most important tourist enclaves of Tenerife and Gran Canaria, located in the municipalities of Arona and Adeje (SW of Tenerife) and in San Bartolomé de Tirajana and Mogán (S-SW of Gran Canaria). In order to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The increased incidence of typhoons or tropical storms due to climate change in coastal destinations obviously puts tourists at risk. Research has shown that cruise ships and airplanes were both negatively affected by the incidence of hurricanes at popular tourist destinations, such as the Caribbean and the Canary Islands (Carballo Chanfón et al , 2021; Yanes Luque et al , 2021). In addition, changes in climate, for instance increased temperature, may also result in conditions like intense heat waves that reduce comfort for tourists (Matzarakis et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The increased incidence of typhoons or tropical storms due to climate change in coastal destinations obviously puts tourists at risk. Research has shown that cruise ships and airplanes were both negatively affected by the incidence of hurricanes at popular tourist destinations, such as the Caribbean and the Canary Islands (Carballo Chanfón et al , 2021; Yanes Luque et al , 2021). In addition, changes in climate, for instance increased temperature, may also result in conditions like intense heat waves that reduce comfort for tourists (Matzarakis et al , 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This means that more directions must be considered to construct a port in the Canary Islands, than for a port on the continent. In addition, when sizing a structure subject to wave action, it is necessary to know or estimate the significant wave height associated with a certain probability of exceedance within the lifespan of the infrastructure [5]. To determine its design height, it is therefore necessary to model the statistical behaviour of values of significant wave height series that may put the structure at risk.…”
Section: Introductionmentioning
confidence: 99%
“…In coastal areas in particular, previous studies identified some potential biogeophysical hazards to which coastal areas are exposed, including floods, strong winds, coastal erosion, increased salinity of estuaries, alteration of the quality of water available in aquifers, and the disappearance of certain “wet” zones and low-lying coastal fringes [ 4 ]. Storms affecting daily life and the economy in marine and coastal areas were also pointed out by some researchers [ 5 ], calling for better knowledge about the vulnerability and mitigation or adaptation measures that reduce their impact.…”
Section: Introductionmentioning
confidence: 99%